Clustering of Pattern Recognition Receptors for Fungal Detection: e1003873 - Inoue, Makoto; Shinohara, Mari L (PLoS pathogens, 2014)
[...]it has been reported that DC-SIGN synergizes TLR signaling through RAF1, a serine/threonine kinase, which induces phosphorylation of the p65 subunit of NFÎºB, followed by prolonged and enhanced transcription of Il10 by NFÎºB activation [14]. [...]OPN-deficient immunocompromised mice are extremely susceptible to opportunistic infection by Pneumocystis [10]. iOPN is known to co-localize with actin and induces cytoskeletal rearrangement [18], [19].